New 3, 8‐difluoro indoloindole‐based copolymers for organic solar cell. (3rd January 2021) - Lee, Gyeong Seok; Shin, Hee Jeong; Shome, Sanchari; Park, Ji‐Hyun; Ko, Seo‐Jin; Choi, Hyosung; Kim, Yun‐Hi
Summary: The performance of an array of donor‐acceptor based bulk heterojunction (BHJ) polymer solar cells (PSC) containing indoloindole as a key donor block with varying degrees of fluorinated benzothiadiazole (BT) as an acceptor block is reported. Fluorination of BT can enhance crystallinity and planarity of the polymer backbone due to intramolecular F‐S interactions. This also leads to deeper highest occupied molecular orbital (HOMO) energy levels leading to high J SC and V OC . The PSC properties of this series of new copolymer donors blended with fullerene acceptors show a homogeneous and uniform fibrous network in the blend film. The most homogeneous film was achieved with monofluorinated BT (PFDHI‐TFT) that resulted in better charge extraction pathway leading to high power conversion efficiency (PCE). The solar cell using PFDHI‐TFT as donor and fullerene acceptor showed PCE of 5.98% with V OC of 0.80 V, J SC of 10.56 mA cm −2, and fill factor (FF) of 0.71, respectively, under AM 1.5G illumination (100 mW cm −2 ) in the absence of annealing. Abstract : The performance of an array of donor‐acceptor based bulk heterojunction (BHJ) polymer solar cells (PSC) containing indoloindole as a key donor block with varying degrees of fluorinated benzothiadiazole (BT) as an acceptor block is reported. Fluorination of BT can enhance crystallinity and planarity of the polymer backbone due to intramolecular F‐S interactions.